2019
DOI: 10.3354/meps12939
|View full text |Cite
|
Sign up to set email alerts
|

Effect of suspended sediments on the pumping rates of three species of glass sponge in situ

Abstract: The largest known glass sponge reefs in Canada are within the Hecate Strait and Queen Charlotte Sound Glass Sponge Reefs Marine Protected Area (HSQCS-MPA) in British Columbia. However, human activities outside the core MPA boundaries, such as trawling, can create plumes of suspended sediments capable of travelling large distances. We studied the response of 3 glass sponge species to changes in suspended sediment concentrations (SSCs) at 170 m depth inside the HSQCS-MPA. Two species reduced excurrent flow rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 55 publications
2
38
0
Order By: Relevance
“…Reiswig found that sponge-pumping behavior was more complex than previously thought and might be driven by both abiotic (e.g., storms, sedimentation, and temperature) and intrinsic factors (e.g., daily cycles and behavioral pattern). More recent studies focused on the effect of a single parameter on the sponge pumping in either laboratory conditions (e.g., Annandale, 1907;Stuart and Klumpp, 1984;Huysecom et al, 1988;Riisgård et al, 1993;Larsen and Riisgård, 1994;Tompkins-MacDonald and Leys, 2008;Pfannkuchen et al, 2009;Schläppy et al, 2010;Massaro et al, 2012;Lavy et al, 2016;Strehlow et al, 2016;Kumala et al, 2017;Kumala and Canfield, 2018;Goldstein et al, 2019) or in situ (e.g., Gerrodette and Flechsig, 1979;Savarese et al, 1997;Bell et al, 1999;Trussell et al, 2006;Tompkins-MacDonald and Leys, 2008;Schläppy et al, 2010;Leys et al, 2011;McMurray et al, 2014;Lewis and Finelli, 2015;Ludeman et al, 2017;Grant et al, 2019;Wooster et al, 2019). Unfortunately, most studies were short term or small scale and thereby failed to provide a comprehensive view of the long-term in situ natural pumping behavior of the studied sponges.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reiswig found that sponge-pumping behavior was more complex than previously thought and might be driven by both abiotic (e.g., storms, sedimentation, and temperature) and intrinsic factors (e.g., daily cycles and behavioral pattern). More recent studies focused on the effect of a single parameter on the sponge pumping in either laboratory conditions (e.g., Annandale, 1907;Stuart and Klumpp, 1984;Huysecom et al, 1988;Riisgård et al, 1993;Larsen and Riisgård, 1994;Tompkins-MacDonald and Leys, 2008;Pfannkuchen et al, 2009;Schläppy et al, 2010;Massaro et al, 2012;Lavy et al, 2016;Strehlow et al, 2016;Kumala et al, 2017;Kumala and Canfield, 2018;Goldstein et al, 2019) or in situ (e.g., Gerrodette and Flechsig, 1979;Savarese et al, 1997;Bell et al, 1999;Trussell et al, 2006;Tompkins-MacDonald and Leys, 2008;Schläppy et al, 2010;Leys et al, 2011;McMurray et al, 2014;Lewis and Finelli, 2015;Ludeman et al, 2017;Grant et al, 2019;Wooster et al, 2019). Unfortunately, most studies were short term or small scale and thereby failed to provide a comprehensive view of the long-term in situ natural pumping behavior of the studied sponges.…”
Section: Discussionmentioning
confidence: 99%
“…A high rate of sedimentation (>7 mg L −1 ) was documented to induce a reduction in sponge pumping, sometimes to a complete cessation (Reiswig, 1971;Gerrodette and Flechsig, 1979;Leys and Lauzon, 1998;Tompkins-MacDonald and Leys, 2008;Grant et al, 2018Grant et al, , 2019. Other than in the course of winter storms, during which no sampling took place, our oligotrophic study area was typified with clear water (visibility >10 m) and low concentrations of suspended sediment (Ribes et al, 1999b).…”
Section: Environmental Factors Affecting Pumping Ratementioning
confidence: 99%
“…Although all reefs in this study are now protected from bottom-contact fishing activities (DFO, 2015(DFO, , 2017(DFO, , 2019, other anthropogenic stressors might affect these systems. For example, increased sedimentation, such as that caused by trawling near protected area boundaries, may disrupt filter-feeding of reef-building sponges, resulting in decreased growth or increased mortality (Grant et al, 2019). Additionally, there is now evidence that increasing water temperatures and ocean acidification may impact reef sponges' ability to feed, resulting in tissue necrosis and, potentially, starvation (Stevenson et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Ambient water is drawn through numerous inhalant openings (ostia) into an incurrent canal system, where it enters many choanocyte chambers (CCs) through prosopyles, passes microvillar collar-sieves, exits the CC through apopyles and leaves the sponge via an excurrent canal system that finally leads to an exhalant opening, the osculum (Larsen and Riisgård, 1994). Contractions can effectively restrict or stop the water flow through a sponge (Reiswig, 1971;Riisgård et al, 2016;Kumala et al, 2017;Ludeman et al, 2017;Goldstein et al, 2019) and have been suggested to protect the filter-pump, for instance during periods with high loads of re-suspended sediment (Elliott and Leys, 2010;Bannister et al, 2012;Leys, 2015;Grant et al, 2019).…”
Section: Introductionmentioning
confidence: 99%